2022
DOI: 10.1021/acs.orglett.2c02537
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Direct C–H Glycosylation of Free (N-H) Indole and Tryptophan by Norbornene-Mediated Regioselective C–H Activation

Abstract: We describe the palladium-catalyzed direct C−H glycosylation of free N-H indole or tryptophan for the stereoselective synthesis of 2-glycosylindoles and tryptophan-C-glycosides. This reaction relies on the ortho-directing transient mediator norbornene, which underwent regioselective C−H functionalization at the indole or tryptophan ring, providing high chemoselectivity. This method offers a more straightforward, stepeconomical, and cost-effective route to construct C-glycosides. The gram-scale amenable buildin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The mechanism study showed that the 2,3‐diglycosylation sequence of indole was C3, followed by C2. Based on these, Mandal group [28] described that naked N−H indole or tryptophan 60 synthesized a series of 2‐glycosylindoles and tryptophan‐C‐glycosides 62 through Pd catalyzed C−H glycosylation strategy. Norbornene plays an important role in this method, providing high chemoselectivity for indole by acting as an ortho ‐directing transient mediator 63 .…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism study showed that the 2,3‐diglycosylation sequence of indole was C3, followed by C2. Based on these, Mandal group [28] described that naked N−H indole or tryptophan 60 synthesized a series of 2‐glycosylindoles and tryptophan‐C‐glycosides 62 through Pd catalyzed C−H glycosylation strategy. Norbornene plays an important role in this method, providing high chemoselectivity for indole by acting as an ortho ‐directing transient mediator 63 .…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, Liang and co-workers successfully applied a structurally modified NBD for the synthesis of C4 -glycoside indole . Mandal’s group recently reported a palladium-catalyzed stereoselective synthesis of 2-glycosylindoles and tryptophan- C -glycosides via NBE-mediated C–H activation . Despite much great progress in this field, the development of a highly efficient, general, and convenient strategy leading to indolyl- C -glycosides from readily available starting materials is still highly valuable.…”
mentioning
confidence: 99%
“…Even if 4.0 equiv of glycosyl chlorides are used, the single bis- C -mannosylated indole could not be attained. Moreover, many elegant strategies employing transition-metal-catalyzed C–H glycosylation were subsequently developed by the groups of Chen and He, , Liang and Liu, Liu, Akermann, and others . But to the best of our knowledge, ferrocene derivatives have not been employed for this C–H glycosylation so far .…”
mentioning
confidence: 99%